Murine CXCR3+CXCR6+γδT Cells Reside in the Liver and Provide Protection Against HBV Infection - Wang, Yanan; Guan, Yun; Hu, Yuan; Li, Yan; Lu, Nan; Zhang, Cai (Frontiers in Immunology, 2022)
Gamma Delta (γδ) T cells play a key role in the innate immune response and serve as the first line of defense against infection and tumors. These cells are defined as tissue-resident lymphocytes in skin, lung, and intestinal mucosa. They are also relatively abundant in the liver, however, little is known about the residency of hepatic γδT cells. By comparing the phenotype of murine δT cells in liver, spleen, thymus, and small intestine, a CXCR3+CXCR6+ δT cell subset with tissue-resident characteristics was found in liver tissue from embryos through adults. Liver sinusoidal endothelial cells mediated retention of CXCR3+CXCR6+ γδT cells through the interactions between CXCR3 and CXCR6 and their chemokines. During acute HBV infection, CXCR3+CXCR6+ γδT cells produced high levels of IFN-γ and adoptive transfer of CXCR3+CXCR6+ γδT cells into acute HBV infected TCRδ-/- mice led to lower HBsAg and HBeAg expression. It is suggested that liver resident CXCR3+CXCR6+ γδT cells play a protective role during acute HBV infection. Strategies aimed at expanding and activating liver resident CXCR3+CXCR6+ γδT cells both in vivo or in vitro have great prospects for use in immunotherapy that specifically targets acute HBV infection.